MENGELOLA RISIKO PROYEK PENGEMBANGAN SOFTWARE - Putro, Endi; Ariesta, Maria (Teknik dan Ilmu Komputer, 2012)
Software Development is considered as a project due to the budget and time restrictions applied to it. Â In software development project, risk refers to an event that is not in the plan which may occur and result in the project loss. The methodology used to manage the project risks include giving weigth to the matrix that draws together the project management activities and questions generated based on the risk factors of software development projects. The results of these matrixes are used to anticipate the risks that might appear during the project implementation. Â Keywords: project, risk, managing